Convenient Synthesis of Heterocyclic Azo Dyes in the Class of Pyranopyrazoles and Chromenes. (February 2018) - Arbabi, Hamidreza Azari; Soltani, Siavash Salek; Salehi, Hasan; Rezazadeh, Shahla; Zonouzi, Afsaneh; Toosibashi, Mansoureh
A series of novel azo group fused 2 H -chromenes and 4 H -chromenes were synthesised as well as pyranopyrazole derivatives via the Knoevenagel condensation reaction of C–H acid compounds with 5-(arylazo)salicylaldehydes by a nucleophilic addition to the carbonyl group followed cyclisation.